Agricultural mechanization and south-south knowledge exchange: What can Ethiopian and Kenyan policymakers learn from Bangladesh’s experience? - Animaw, Addisu Tadege; Nkanya, Jasper Alfred Mutegi; Nyakiba, John Mogaka; Woldemariam, Tamiru Habte; Takeshima, Hiroyuki (International Food Policy Research Institute, 2016)
This note synthesizes one of the two study tour reports written by the participating African officials. This report provides observations made by participants from Ethiopia and Kenya, the two East African countries with participants on the tour.